Design and Optimization of Proton Exchanged Integrated Electro-Optic Modulators in X-Cut Lithium Niobate Thin Film - Huangpu Han; Bingxi Xiang; Tao Lin; Guangyue Chai; Shuangchen Ruan (Crystals, 2019)
In this study, we designed, simulated, and optimized proton exchanged integrated Mach-Zehnder modulators in a 0.5-μm-thick x-cut lithium niobate thin film. The single-mode conditions, the mode distributions, and the optical power distribution of the lithium niobate channel waveguides are discussed and compared in this study. The design parameters of the Y-branch and the separation distances between the electrodes were optimized. The relationship between the half-wave voltage length production of the electro-optic modulators and the thickness of the proton exchanged region was studied.